PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI TERAPI MULTIMEDIA DENGAN METODE LOVAAS DI SLB B YPLB DANYANG PURWODADI - Sutiyono; Sarah Wahyu Agustini; Yulianasari; Putri Melli Anjani (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2021)
One way to increase the degree of education in special schools is to use interactive learning. One of the media used is multimedia-based lovaas media. The purpose of learning with multimedia is to be more effective and learning to be more fun. The Lovaas method that will be implemented will follow the curriculum from the school although in the application of the Lovaas method there are still many that have not been developed in schools, especially SLB YPLB Danyang Purwodadi.   Purpose   The purpose of this learning method is to provide teaching in the provision of stimuli (instructions), individual responses (behavior) and consequences (behavioral consequences).   Method:   The method used in this service is to use the method introduction stage, learning method training and mentoring of learning methods to students. The location of this service is SLB YPLB Danyang Purwodadi   Results   The results of service in the learning method can be seen from the learning outcomes from the socialization of the 100% running learning program, 100% instructional education from instructions, 100% behavioral responses, and the consequences and results of 100% lovass method learning.   Conclusion:   There is a better change in the stimulus (instruction), individual response (behavior) and consequences (behavior) of the learning method using the Lovaas method for students, especially SLB YPLB Danyang Purwodadi